ナンキョク ミナミ ビクトリアランド ノ ラビリンス ニ オケル チスイ チュウ ノ エン キイン リチウム ト ホウソ カラ ノ コウサツ - 高松, 信樹; タカマツ, ノブキ; 松本, 源喜; マツモト, ゲンキ; 中谷, 周; ナカヤ, シュウ; 鳥居, 鉄也; トリイ, テツヤ; Takamatsu, Nobuki; Matsumoto, Genki I.; Nakaya, Shyu; Torii, Tetsuya (1988)
P(論文) 南極南ビクトリアランド・ドライバレー地域・ラビリンス(77°33′S, 160°50′E)の池水中の塩起因を明らかにするため, LiとB含量を測定した。また, これらと比較するため, ドライバレー地域のバンダ湖, ドンファン池, フリクセル湖およびボニー湖ならびにベストフォールドヒルズのディープ湖とエース湖についても同様の測定を行った。ラビリンスの淡水および塩水中のLiおよびBの濃度および濃縮係数などより, 池水の化学成分は海水や熱水起源ではなく, おもに風送塩に起因するものであることが明らかになった。これらのことはラビリンスの塩水池が風送塩を含む氷河氷や雪の融水が凍結濃縮を繰り返すことによって形成されたとする考えを支持している。塩化物イオン含量の増加とともにB/Cl比が減少することから, Bは凍結過程で氷に移行し, 蒸発によって徐々に揮発していくと考えられる。 Lithium and boron contents in pond waters of the Labyrinth (77°33′S, 160°50′E) of the Dry Valleys region in Southern Victoria Land, Antarctica were determined to elucidate the origin of dissolved salts. Also Lakes Vanda, Fryxell and Bonney, and Don Juan Pond in the Dry Valleys region as well as Deep and Ace Lakes in the Vestfold Hills were studied for comparison. The contents and enrichment factors of Li and B in both freshwater and saline ponds in the Labyrinth reveal that major ionic components in the pond waters originate mainly from atmospheric salts, rather than from trapped seawater and/or hydrothermal waters. These results support that the saline pond waters in the Labyrinth can be formed by the successive concentration through evaporation of pond waters supplied from glacial ice and/or snow containing atmospheric salts. The decrease of B/Cl ratios with the increase of chloride ion contents implies strongly that B is transported into ice during freezing of pond water, then volatilizes gradually to the atmosphere under frigid conditions. departmental bulletin paper